New Manufacturing Method of Glass Foam by Cold Expansion of Glass Waste - Lucian Paunescu; Sorin Mircea Axinte; Bogdan Valentin Paunescu (Newinera Publisher, 2021)
Abstract An innovation cold manufacturing method of glass foams is presented in the paper. Traditional foaming agents used in conventional expansion processes of glass waste at high temperature were substituted with aluminium powder in aqueous solution of calcium hydroxide, which releases hydrogen forming gas bubbles in the viscous sludge and then, by solidification, a porous structure typical for the glass foam. The manufactured foam is adequate for using as a thermal insulation material for inner wall of buildings, having the apparent density of 0.31 g·cm-3, the thermal conductivity of 0.070 W/m·K and the compressive strength of 1.32 MPa. The process originality is the use of recycled aluminum waste, melted by an own microwave heating technique and sprayed with nitrogen jets. The process effectiveness is remarkable in economical and energy terms.